PENGARUH ELECTRONIC WORD OF MOUTH DAN CELEBRITY ENDORSMENT TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Jayanti, Dinda Dwi; Welsa, Henny; Cahyani, Putri Dwi (2020)
This study aims to determine: (1) the effect of electronic word of mouth on brand image, (2) the influence of celebrity endorsment on brand image, (3) the effect of electronic word of mouth on purchase intention, the effect of celebrity endorsment on purchase intention, (5) the effect of brand image on purchase intention (6) the effect of electronic word of mouth on purchase intention with brand image as an intervening variable, (7) the influence of celebrity endorsement on purchase intention with brand image as an intervening variable case in users of naava green skin care products in Yogyakarta Branch . This research uses a quantitative approach by collecting data through questionnaires. The population in this study were users of naava green skin care products in Yogyakarta Branch. The sampling technique uses a non probability sampling method that is purposive sampling. The sample was 115 respondents with data collection techniques using a questionnaire. Data analysis techniques in this study used descriptive analysis techniques, multiple linear regression and multiple test.